Education for global justice: Themes, aims and criteria for transformative education - Muñoz-Saavedra, Judith; Galdames-Calderón, Marisol (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Global Justice Education is a critical and transformative educational proposal promoted by the Catalan Federation of Global Justice Organizations (LaFede.Cat), although it is a widespread approach, its conceptual framework is underdeveloped. The article aims to define thematic/methodological criteria that allow the identification and characterization of global justice educational practices. The methodology corresponds to a process of systematization and organization of the experiences of the organizations using qualitative interviews, focus groups and documentary analysis. The results show six thematic lines and five theoretical/methodological criteria that can illustrate and guide those who wish to learn about or adopt the approach.